KESANTUNAN BERBAHASA DALAM FILM HABIBIE & AINUN - Arianti, Ni Kadek (Humanis; Volume 15. No.1. April 2016)
This study aims at (1) describing the politeness strategies of Habibie & Ainunfilm , (2) finding and describing the politeness factors of Habibie & Ainunfilm . This study used the theory of politeness were proposed by Brown and Levinson . The data were c ollect ed through observ ation attentively method assis ted with notes and sorting technique. The collected datas were descriptively analyzed by applying qualitative descriptive method. The results of this study are describing politeness strategies , namely positive politeness strategy and negative politeness strategies. In addition, politeness Habibie & Ainun film is influenced by several factors, namely social status, age,and gender factors.
Keywords: film, politeness strategies, and politeness factors